Khat power. The political life of a stimulating plant - (:unkn) unknown (My University, 2019)
A plant with psychotropic properties, khat has been legally cultivated and consumed in the Horn of Africa for centuries, and illegally follows the East African diaspora around the world. From the market stalls of Muslim Ethiopia to a customs seizure in Calais, Céline Lesourd follows the trajectories of an ambivalent commodity: as it crosses borders and exposes itself to new moral bastions, catha edulis becomes a drug prized by immigrants and is said to finance Islamic terrorism. For farmers, wholesalers, traders and former smugglers, the economic and political stakes of an international trade are taking shape. For consumers, it's the social distinctions, sexual fantasies and exaltations of identity and religion that (re)crystallise around this branch. From yesterday to today, between the intimate and the global, this survey reveals what men do with khat and what khat - in a globalised market - does to men. And even more so, to women.
Keywords: African Research